The use of transvaginal ultrasound alters physiologic uterine peristalsis in gynecologic participants - Kelsey Anderson, M.D; Sicheng Wang, Ph.D; Stephanie Pizzella, M.S; Qing Wang, Ph.D; Yong Wang, Ph.D; Valerie Ratts, M.D (Elsevier, 2024)
Objective: To study whether transvaginal ultrasound (TVUS) affected the uterine peristalsis (UP) patterns in nonpregnant participants. Design: Institutional review board-approved, prospective observational cohort study. The noninvasive UP imaging (UPI) system uses electrode patches placed on the patient's skin just above the pubic bone and on the low back to quantify the 3-dimensional electrical activation pattern during UP by calculating peristalsis frequency, duration, magnitude, and activation ratio. A 20-minute UPI scan was completed without TVUS followed by a 10-minute UPI scan acquired simultaneously during TVUS examination as a comparison. Setting: University medical center. Patient(s): Twenty-eight participants with regular menstrual cycles not taking hormonal medication and with a normal uterus were included in analysis. Intervention(s): Subjects were imaged longitudinally during the four phases of the menstrual cycle (menses, proliferative, periovulatory, and secretory) with a UPI scan followed by concurrent TVUS and UPI scan. Serum hormone levels (estradiol and progesterone) and TVUS evaluating follicular development were obtained during each visit to confirm menstrual cycle phase. Main Outcome Measure(s): Duration, frequency, magnitude, and activation ratio of the UP waves. Result(s): With the use of simultaneous TVUS, UP waves had a change in at least one of the outcomes measured in all visits. The frequency, magnitude, and duration were significantly higher with TVUS use in all phases of the menstrual cycle. The activation ratio was higher with TVUS during all phases except the periovulatory phase. Conclusion(s): This study demonstrated that TVUS may inherently affect UP waves. Therefore, noninvasive technology may more accurately measure physiologic peristalsis waves.